A Tour‐Guide through Carbon Nitride‐Land: Structure‐ and Dimensionality‐Dependent Properties for Photo(Electro)Chemical Energy Conversion and Storage. Issue 4 (11th July 2021) - Lau, Vincent Wing‐hei; Lotsch, Bettina V.
Abstract: Despite the explosion in the number of publications on the graphitic carbon nitride family of materials, much still remains unknown about their structure and the underlying properties responsible for their various applications. This critical review covers the state‐of‐the‐art in the understanding of their structure–property–photocatalysis relationship, from their molecular constituents to stacking as a (quasi) two‐dimensional structure, highlighting the areas in which there is wide agreement and those still unresolved. This review first recounts how the structural understanding of these materials has evolved since the 19th century, followed by a commentary on the best practice for unambiguously characterizing their molecular structure and two‐dimensional stacking arrangements. The recent literature is then examined to elucidate how individual molecular moieties affect their various material properties, particularly their chemical and opto–electronic properties, carrier dynamics, and catalytic reactivity, and how their use for energy applications can be impacted by the structural features across each dimension. Lastly, the translation of the aforementioned fundamental insights to rational molecular design is demonstrated, highlighting the synthesis of heptazine‐based materials for order‐of‐magnitude improvement in photocatalytic reactivity, as well as the unusual phenomenon of stabilization of light‐induced electrons, an effect currently exploited for a new paradigm in solar energy storage. Abstract : This article reviews the current understanding of the structure–property–function relationship of the graphitic carbon nitride family of materials, covering their historical developments, characterization methodologies, chemical and opto–electronic properties, carrier dynamics, and catalytic reactivity. The focus is on the materials' structures across three dimensions as the origin of these properties, highlighting topics on which there is a consensus, and those still contentious for future research.